2017
DOI: 10.1002/aur.1844
|View full text |Cite
|
Sign up to set email alerts
|

Normative data and psychometric properties of a farsi translation of the strange stories test

Abstract: This new translation of the Strange Stories test is a reliable and valid instrument to evaluate higher level theory of mind abilities in community samples of Farsi speaking children. Autism Res 2017, 10: 1960-1967. © 2017 International Society for Autism Research, Wiley Periodicals, Inc. LAY SUMMARY: "Mentalizing" or "theory of mind," the ability to recognize others' mental states, is a key aspect of social understanding. Mentalizing problems are characteristic of some clinical conditions such as autism. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…This finding is consistent with other literature where it has been suggested that females were better in understanding social situations and intentions (Białecka-Pikul et al, 2017) and adds to the construct validity data of the relationships between ToM and gender (e.g. Calero et al, 2013; Shahrivar et al, 2017). In terms of concurrent validity (as part of criterion validity to answer research question 3), there are significant correlations among the Y-ToM social and physical scores with the Happé’s Strange Stories social and physical scores.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with other literature where it has been suggested that females were better in understanding social situations and intentions (Białecka-Pikul et al, 2017) and adds to the construct validity data of the relationships between ToM and gender (e.g. Calero et al, 2013; Shahrivar et al, 2017). In terms of concurrent validity (as part of criterion validity to answer research question 3), there are significant correlations among the Y-ToM social and physical scores with the Happé’s Strange Stories social and physical scores.…”
Section: Discussionsupporting
confidence: 92%
“…The Strange Stories test has been adapted as a Farsi (paper-and-pen format) translation for an Iranian community sample of school-aged children aged 9–11 (Shahrivar et al, 2017) and also been adapted as a video version to assess ToM in Australian sample of adults (mean age of 27 years old) with ASD (Brewer et al, 2017). Expanding available advanced ToM tools in an Asian context could be a good reason to adapt the Strange Stories to understand the development of advanced ToM in the light of cultural differences (Perez-Zapata et al, 2016; Slaughter & Perez-Zapata, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But numerous studies document failures of prediction. For example, performance on theory-of-mind tasks fails to significantly predict autistic traits in either autistic or nonautistic participants , as measured by clinicians’ observation, self-report, or informant-report ( N = 1513 nonautistic adults, Kunihira, Senju, Dairoku, Wakabayashi, & Hasegawa, 2006; N = 638 nonautistic children, Ronald, Viding, Happé, & Plomin, 2006; N = 395 autistic adults, Lombardo et al, 2015; N = 220 nonautistic adults, Ragsdale & Foley, 2011; N = 206 nonautistic men, Voracek & Dressler, 2006; N = 194 autistic and 60 nonautistic children, Scheeren et al, 2013; N = 178 autistic men, 168 nonautistic women, and 152 nonautistic men, Baron-Cohen et al, 2015; N = 108 nonautistic adults, Melchers, Montag, Markett, & Reuter, 2015; N = 100 autistic adolescents, Lukito et al, 2017; N = 100 autistic adolescents, Jones et al, 2018; N = 89 autistic and 89 nonautistic adults, Wilson et al, 2014; N = 79 nonautistic women, Valla et al, 2010; N = 56 autistic children, Salter, Seigal, Claxton, Lawrence, & Skuse, 2008; see similar results with smaller samples in Bryant, Coffey, Povinelli, & Pruett, 2013; Burnside, Wright, & Poulin-Dubois, 2017; Clemmensen et al, 2016; Dziobek et al, 2006; Murray et al, 2017; Ozonoff & McEvoy, 1994) empathy and emotional understanding ( N = 484 nonautistic adults, Olderbak et al, 2015; N = 395 autistic adults, Lombardo et al, 2015; N = 342 nonautistic adolescents, Sharp & Vanwoerden, 2014; N = 220 nonautistic adults, Ragsdale & Foley, 2011; N = 200 nonautistic adults, Vellante et al, 2013; N = 178 autistic men, 168 nonautistic women, and 152 nonautistic men, Baron-Cohen et al, 2015; N = 162 nonautistic adults, Ferguson & Austin, 2010; N = 121 nonautistic adolescents and adults, Gökçen, Frederickson, & Petrides, 2016; N = 108 nonautistic adults, Melchers et al, 2015; N = 89 autistic and 89 nonautistic adults, Wilson et al, 2014; N = 58 nonautistic children, Tsang, Gillespie-Lynch, & Hutman, 2016; N = 53 nonautistic adults, Lawrence et al, 2004; see similar results with smaller samples in Carroll & Chiew, 2006; Campbell et al, 2011; Muller et al, 2010; Peterson, 2014) everyday social skills ( N = 398 nonautistic children, Shahrivar, Tehrani-Doost, Khorrami Banaraki, Mohammadzadeh, & Happé, 2017; N = 164 and 140 nonautistic adults, Ames & Kammrath, 2004; N = 124 nonautistic adolescents, Botting & Conti-Ramsden, 2008; N = 101 nonautistic children, Lunn, Lewis, & Sher...…”
Section: Failures Of Predictive Validitymentioning
confidence: 53%
“…everyday social skills (N ϭ 398 nonautistic children,Shahrivar, Tehrani-Doost, Khorrami Banaraki, Mohammadzadeh, & Happé, 2017; N ϭ 164 and 140 nonautistic adults,Ames & Kammrath, 2004; N ϭ 124 nonautistic adolescents, Botting & Conti-Ramsden, 2008; N ϭ 101 nonautistic children, Lunn, Lewis, & Sherlock, 2015; N ϭ 97 nonautistic children, Lew et al, 2015; N ϭ 65 nonautistic children, Raud et al, 2015; N ϭ 63 nonautistic adults, Stanford, Messinger, Malaspina, & Corcoran, 2011; N ϭ 60 nonautistic children, Raud et al, 2015; N ϭ 53 nonautistic adults, Chen et al, 2017; N ϭ 50 nonautistic adults, McCleery et al, 2012; see similar results with smaller samples of autistic children and adults in…”
mentioning
confidence: 99%